Vygotsky’s “Thought” in Linguistic Meaning - Ruthrof, Horst (Rivista Italiana di Filosofia del Linguaggio, 2012)
Central to Vygotsky’s theory of language acquisition, the paper claims, is his complex notion of ‘thought’  straddling as it does mental events from pre-predicative thinking to the full social conceptuality of modern culture. In support of this reading the paper foregrounds two features in Vygotsky’s theory, his social gradualism, characterized by his emphasis on historical cultural processes, and the prominence in his argument of mental resemblance relations in the development of the child’s mastery of meaning. Vygotsky is shown to defend the position that there is an important link between nonverbal cognition and language, between perception and word. This, the paper argues, makes Vygotsky’s enterprise compatible with a semantics of imaginability, a claim backed up by his observation that in language it is the imaginary apple rather than the real one that is decisive. As a psychological system, the imagination certainly plays a crucial role in one of Vygotsky’s central concerns: concept formation from syncretism via endophasy towards mature conceptuality. The paper concludes with Vygotsky’s view of linguistic meaning as generalized reflection of reality in contrast to definitional conceptions which sever the concept from its ‘natural connections